Inhibition of mouse and rat lymphoproliferation by gangliosides - Montero, Edna Frasson de Souza [UNIFESP] (2000)
Our previous study have demonstrated that Glycosphingolipids (GSLs) have an immunosuppressive effect on murine lymphoproliferation and IL-2 production. In the present study we examined the effect of a pool of Gangliosides (Gang) on spleen lymphocyte proliferation from either isogeneic strains of Wistar rats or BALB/c mice. Two hundred-fifty grams adult female isogeneic Wistar rats and 8-week-old BALB/c mice were used. The animals were sacrificed and the spleen harvested aseptically for cellular assays. Spleen cells suspensions were obtained by homogenization in RPMI 1640 with a loose tissue grinder. After washing, the cells were suspended in RPMI 1640 supplemented. Cell viability was measured by Trypan blue exclusion. Cells were cultured in triplicate using increasing concentrations of Gang (1; 2; 5; 10; 15; 20 mug/well) and in the presence of Concanavalin A. The cells were incubated for 48 hours and were pulsed with [³H] thymidine 18 hours prior to harvesting on glass fiber paper for counting in a beta-counter. Data were presented as rate of inhibition, as previously described. At concentrations 1 and 2 mug/well, Gang stimulated lymphoproliferation (30% and 50%, rats and mice respectively), while at concentration from 5 to 20 mug/well an increasing inhibition was observed for spleen cells from both mouse and rat (from 40% up to 80%). In preliminary studies we observed inhibition of mixed lymphocyte reaction on spleen cells from rats treated with Gang for 10 days (data not shown). Our data suggest that Gang may be investigated as a immunosuppressive drug in organ transplantation.